Sweet insanity - MTI video (MTI Video, 2006)
Stacey is a typical high school senior - she sits through boring school classes during the week so she and her friends can party on the weekend. Then she meets Christina, the new girl in school. Christina's friendship with Stacey quickly grows, until it borders on the obsessive. And something from Christina's past has followed her to her new school - something dark and sinister. Suddenly, a popular classmate disappears and a chain of deadly events is set in motion leaving Stacey to confront an impossible evil.
Mackenzie Firgens, David Fine, Rebekah Isaacs.
MPAA : R for Strong violence, language, teen drug and alcohol use and sexuality.
Keywords: Horror films; Feature films